High sulfur content in distillers grains alters ruminal fermentation and diet digestibility in beef steers - Uwituze, S.; Parsons, G.L.; Karges, K.K.; Gibson, M.L.; Hollis, Larry C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Requirements for elemental sulfur in feedlot diets have been established to be approximately 0.15% with a maximum upper threshold of 0.40% of diet dry matter. Feeding ethanol fermentation by-products, such as distillers grains with solubles, that are high in sulfur can result in dietary sulfur levels that exceed the recommended maximum. Previous studies indicated that dietary sulfur influenced the site and extent of fiber and protein digestion. The objective of this study was to evaluate ruminal fermentation characteristics and diet digestibility when 30% (dry matter basis) dried distillers grains with solubles with various levels of sulfur was incorporated into finishing diets based on steam-flaked corn or dry-rolled corn.
Keywords: Beef; Sulfur; Distillers grains; Ruminal fermentation; Digestibility